Smart Drug Delivery Systems Based on Single-Wall Carbon Nanotubes Loaded with Nanocurcumin Extract for Cancer Therapy and Toxicity - Marwa R. Jwameer; Sabah A. Salman; Farah T. M. Noori (Academic Science Journal)
The main objective of the study is to prepare smart drug delivery systems based on single-wall carbon nanotubes. In this study, nanocurcumin (N.Cur) was loaded onto SWCNTs containing polyethylene glycol (PEG) and polyethyleneimine (PEI), which includes amino groups — this led to the successful production of PEG-PEI-SWCNTs. XRD, UV-Vis, and TEM techniques were employed to investigate the spectral and structural properties of (PEG-PEI-SWCNTs-N.Cur). The PEG-PEI-SWCNTs showed distinct crystalline structures and flaws, as well as a larger interlayer spacing, as evidenced by XRD patterns. After loading N. Cur, TEM analysis confirmed the presence of curcumin extract. UV-Vis absorbance peaks at 289, 300.98, (282,425), and (273,431) nm appear to be linked to SWCNTs, PEG-PEI-SWCNTs, N. Curcumin extract, and PEG-PEI-SWCNTs-N, respectively. After exposure to a variety of produced SWNTs and PEG-PEI-SWCNTs at concentrations ranging from 6.25 to 100 g/ml for 72 hours, the rate of growth inhibition in cancer cells including the liver cancer HepG2 cell line—was assessed. The cancer cells were found to be very dangerous by the cytotoxicity testing.